Role of Plasmapheresis in the Treatment of Severe Pruritus in Pregnant Patients with Primary Biliary Cirrhosis: Case Reports - Alallam Alallam; David Barth; E Jenny Heathcote (Canadian Journal of Gastroenterology)
BACKGROUND: Primary biliary cirrhosis (PBC) may be associated with pruritus and, when present, may be accentuated during pregnancy. Several therapeutic modalities have been used to control itching caused by cholestasis, with variable responses. Drug therapies are ill-advised, particularly in early pregnancy. Plasmapheresis has been successful in controlling pruritus in patients with cholestasis. The use of plasmapheresis to alleviate severe life-threatening pruritus during pregnancy is reported in two patients with PBC.